Electricity Token Charging Based on Internet of Things - Darmono, Hendro; Waluyo, Waluyo; Suharto, Nugroho; Koesmarijanto, Koesmarijanto (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Many prepaid electricity meters have been implemented for new and existing customers, and these meters offer advantages over conventional meters. Purchasing token pulses on prepaid electricity meters can be done anytime and anywhere, making it more practical and easier for customers to recharge electricity vouchers. Customers can purchase electricity tokens at available counters or through an application, and they can add KWh inventory as needed. The use of electricity tokens depends on the power consumption in each household, and the remaining KWh can be viewed on the screen of the prepaid meter. However, customers must enter a 20-digit code every time they recharge an electricity voucher. This paper developed the Internet of Things-based electricity token charging system is designed to address the limitations of manual token charging, which requires users to be at home. This system enables remote token charging via a web application, equipped with a sound sensor that sends notifications to a smartphone when the electricity meter alarm sounds, indicating that the KWh balance is nearly depleted. By using an ESP32 microcontroller and relay module, the system controls solenoids to press the numbers on the prepaid meter keypad. This system can operate anytime as long as it is connected to the internet, achieving high accuracy in the token charging process.